A Bibliometric Analysis Eliminating The Conventional Dakwah In Digital Era Using Vos Viewer (Journal of Namibian Studies : History Politics Culture, 2023)
This research reveals that conventional da'wah messages are eliminated by digital media information. The transmission of the behavior of the people of Padang City is more dominantly influenced by digital media information than conventional da'wah messages. The research objective is to provide message information with conventional da'wah being eliminated, the skills of conventional da'i using digital media, and obstacles to conventional da'wah messages in the transmission of behavior in society. VOS Viewer is an online application that can map published research so that you can see new things from a research theme. The research method used is qualitative research with phenomenological methods based on a series of interviews. The results showed that conventional da'wah messages were eliminated by digital media information in transmitting people's behavior, conventional preachers who were not skilled at using digital media packaged da'wah messages and obstacles to conventional da'wah messages in transmitting people's behavior because conventional da'wah was boring, ineffective and did not answer the problem people. Limitations The study was conducted in only one city in Padang, West Sumatra. Innovation in this research provides da’i with knowledge and skills in digital-based preaching. The implications of providing information and guidance for preachers in packaging da'wah messages to transmit people's behavior, so that they contribute significantly to da’i and society and da’i have expertise in preaching by utilizing social media